Increasd mRNA expression of TRAF-6 and MST-4 in the placenta of women with preterm premature rupture of membranes with histological chorioamnionitis - D. Lu; X. Bao; Q. Wang (IMR Press, 2020)
Objectives: To investigate the expression of mammalian Ste20-like kinase 4 (MST-4) and tumour necrosis factor receptor-associated factor 6 (TRAF-6) in placenta from cases with preterm premature rupture of membranes (PPROM) with histological chorioamnionitis (HCA). Methods: Forty PPROM pregnant women and 40 normal controls were recruited. The foetal membranes were examined by haematoxylin-eosin staining and immunohistochemistry (IHC). MST-4 and TRAF-6 mRNA levels were measured by real-time qPCR. Results: IHC showed that the expressions of TRAF-6 and MST-4 in the combined PPROM and intrauterine infection group were significantly stronger than those in the control group and the PPROM group (p < 0.05). RT-qPCR showed that the expression of TRAF6 and MST4 mRNA in the PPROM with HCA group was significantly higher than that in the control group and the PPROM without HCA group (p < 0.05), but there was no significant difference between the latter two groups (p > 0.05). Conclusion: Increased mRNA expression of TRAF-6 and MST-4 are associated with PPROM with HCA, which may provide new detection markers for the early diagnosis of PPROM with HCA.